Physical Activity Interventions for Increasing Objectively Measured Physical Activity Levels in Patients With Chronic Musculoskeletal Pain: A Systematic Review - Oliveira, Crystian B. [UNESP]; Franco, Marcia R. [UNESP]; Maher, Christopher G.; Christine Lin, Chung-Wei; Morelhão, Priscila K. [UNESP]; Araújo, Amanda C.; Negrão Filho, Ruben F. [UNESP]; Pinto, Rafael Z. [UNESP] (Wiley, 2016)
Objective: To investigate whether physical activity interventions increase objectively measured physical activity levels of patients with chronic musculoskeletal pain (e.g., osteoarthritis, low back pain) compared to no/minimal intervention. Methods: We performed a systematic review with meta-analysis searching the Medline, Embase, Cumulative Index to Nursing and Allied Health Literature, SportDiscus, and Physiotherapy Evidence Database (PEDro) databases, and the main clinical trials registries. Quasirandomized or randomized controlled trials investigating the effect of physical activity interventions on objectively measured physical activity levels (e.g., using accelerometers or pedometers) of patients with chronic musculoskeletal pain compared with no/minimal intervention were considered eligible. Analyses were conducted separately for short-term (≤3 months), intermediate (>3 months and <12 months), and long-term (≥12 months) followups. Pooled effects were calculated using the standardized mean difference (SMD), and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was used in summary conclusions. Results: Eight published trials and 6 registered trials were included. For the short-term followup, pooling of 6 trials showed no significant effect (SMD 0.34, 95% confidence interval −0.09, 0.77) between a physical activity intervention and no/minimal intervention. Similarly nonsignificant results were found for the intermediate and long-term followups. The overall evidence according to the GRADE approach was classified as low quality. Conclusion: Our findings suggest that physical activity–based interventions may lead to little or no difference in objectively measured physical activity levels of patients with chronic musculoskeletal pain compared with no/minimal interventions. Given the number of registered trials, the pooled effect found in this review is likely to change once the results of these trials become available.